2021
DOI: 10.1111/cge.14003
|View full text |Cite
|
Sign up to set email alerts
|

Triploid pregnancy–Clinical implications

Abstract: Triploidy is a life‐limiting genetic aberration resulting from an extra haploid set of chromosomes of paternal (diandric triploidy) or maternal origin (digynic triploidy). Triploidy affects around 1%–2% of all conceptions. The majority of cases is miscarried at early developmental stages. In consequence of genomic imprinting, parental origin affects the phenotype of triploid pregnancies as well as the prevalence and spectrum of related maternal complications. Distinctive ultrasound features of both triploid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Fetal-placental disorders, however, might be recognized solely on the basis of fetal ultrasound unless rapid genetic testing is performed. The most important ultrasound finding related to diandric triploidy is multicystic large placenta with a normal-sized fetus with structural anomalies [ 7 ]. Fetal structural anomalies detected in triploidy are extremely heterogenous; central nervous system anomalies are common; cardiac defects are usually severe and complex; and renal abnormalities, including renal agenesis, multicystic kidneys, and hydronephrosis, are also sometimes observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fetal-placental disorders, however, might be recognized solely on the basis of fetal ultrasound unless rapid genetic testing is performed. The most important ultrasound finding related to diandric triploidy is multicystic large placenta with a normal-sized fetus with structural anomalies [ 7 ]. Fetal structural anomalies detected in triploidy are extremely heterogenous; central nervous system anomalies are common; cardiac defects are usually severe and complex; and renal abnormalities, including renal agenesis, multicystic kidneys, and hydronephrosis, are also sometimes observed.…”
Section: Discussionmentioning
confidence: 99%
“…Other minor findings, such as absence of the gall bladder, hypoplastic lungs, omphalocele, syndactyly of the third and fourth fingers or toes, club hands or feet, or polydactyly may be observed. Theca lutein cysts of both maternal ovaries, also known as hyperreactio luteinalis, are frequently seen [ 7 ]. There are other differential diagnoses in early-onset preeclampsia with multiple fetal malformations, multicystic placenta, and/or hyperreactio luteinalis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it was shown that cadherin 11 is predominantly expressed in complete hydatidiform mole ( 20 , 28 ) and preeclampsia can be seen in the first trimester in hydatidiform mole. Similarly, the risk of preeclampsia in the second trimester in triploidy pregnancies is 35% ( 29 ) . It could be speculated that the relationship between preeclampsia risk and hydatidiform mole might be due to the cadherin 11 protein.…”
Section: Discussionmentioning
confidence: 99%